Migrant women in Italy between exclusion and active participation. A gender perspective in inclusion processes - Chiappelli, Tiziana (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
The article exposes some of the results of Parti-GEMI project relating to participatory processes of immigrants, with a special reference to women. In particular, it analyses the situation in Italy in three social areas considered strategic for the assessment of the actual level of participation in local decision-making processes: political domain, educational sector and representation in trade unions. The first part of the article synthetically addresses the institutional and normative framework in Italy in relation to integration policies addressing migrants, while the second part is devoted to the results of the qualitative research field analysis, conducted through in-depth interviews and focus groups with immigrants and stake holders. The last part is devoted to the experimental training program through capacity building methodologies, mentoring and networking strategies put in place to support a group of migrant women in their process of inclusion and activation within social areas of their interest.